Transfer Problem Dynamics: Macroeconomics of the Franco-Prussian War Indemnity - Michael B. Devereux; Gregor W. Smith (Queen's University, Department of Economics, 2005)
We study the classic transfer problem of predicting the effects of an international transfer on the terms of trade and the current account. A two-country model with debt and capital allows for realistic features of historical transfers: they follow wartime increases in government spending and are financed partly by borrowing. The model is applied to the largest historical transfer, the Franco-Prussian War indemnity of 1871-1873. In these three years, France transferred to Germany an amount equal to 22 percent of a year's GDP. When the transfer is combined with measured shocks to fiscal policy and a proxy for productivity shocks over the period, the model provides a very close fit to the historical sample paths of French GDP, terms of trade, net exports, and aggregate consumption. This makes a strong case for the dynamic general equilibrium approach to studying the transfer problem.
Keywords: F32; F41; N14; 330; transfer problem; current account; terms of trade